A utilização da ferramenta eletrônica BACEN CCS e a desconsideração da personalidade jurídica na execução trabalhista : a efetividade da prestação jurisdicional como um direito fundamental - Frank, Marina Silveira (2017)
Currently, it is searched more effectiveness in the jurisdictional provisions. This is verified even more in the labor field, where in one side there is the employee, hyposufficient, and in the other, the employer, that detains the production means and the money. Besides, in this Justice it is deal with food nature funds, which demand more attention and protection by the judge part. Being the employer a juridical person, may the worker suffers loss while trying to obtain his monetary rights, in view of not rare companies are in insolvency state or with low money to pay off debit. So, the theory of disregard of juridical personality surges, not only in the labor field, but initially in the common justice scope, with the objective of preserving creditors’ interests. The use of the institute of disregard of juridical personality, by itself, already match the precepts of labor rights’ unavailability, effectiveness of jurisdiction, besides the procedural celerity and effectiveness necessary to the full accomplishment of withhold fundamental rights. It is undeniable that the electronic tools used in the executory phase of the demand help giving effectiveness to adjudication recognized in the acknowledge phase. Among several existent, which are not object of this study, it is highlighted the one known as “BACEN CCS” (Client Register of the National Financial System), where is possible to identify who manages the company’s bills, even by letter of attorney. In case of existing it, there will be the relative presumption that the subject is partner of the executed part. So, the juridical personality is disregarded so that the patrimony can pay off the debit. For this study, in front of the edition of the new Civil Process Code, 2015 (CPC/2015), still will be necessary to study the innovation brought in its text, in the articles 133 to 137, about the expressed prediction of “juridical personality disregard incident” in the civil process, so as the normative instruction 39/2016 and the article 15 of the CPC/2015, that guide their applicability to Labor Procedural Rights. It will be possible to verify if the labor execution phase is responsible for the lack of effectiveness in the Labor Process and if the electronic tools are capable of assuring the compliance efficiently, mainly for those cases in which the labor complaint would be archived provisionally with debit, circumstance that doesn’t deliver the intended goods of life and, so, doesn’t accomplish the fundamental right to full jurisdiction.